Market Efficiency in Indian Stock Market - Sahani, Rishi (2009)
In this era, efficient market hypothesis has become a very important theory for all the investors who wish to hold or plan to have an international diversified portfolio. As today, all the world economies and markets are globally getting connected, and investors have all the opportunities to invest internationally, so the understanding of market efficiency concept is gaining greater importance for all kinds of investors. In this research I have test the weak form hypothesis and random walk hypothesis for two largest equity markets in India: Bombay stock exchange (BSE) and National stock exchange (NSE). The period of observation in the study is from 2005 to 2008. The results of the tests performed suggest, that the price index do follow random walk model and there is a strong evidence of market accepting weak form efficiency in Indian stock market.